MEMAKSIMALKAN KEPATUHAN PAJAK MENGGUNAKAN TINGKAT PENDIDIKAN DAN TINGKAT PENDAPATAN MELALUI SELF ASSESMENT - Purwantini, Heni; Maharani, Destin Alfianika (UNPERBA, 2025)
The purpose of this study is to analyze the relationship between education level and income level on tax compliance through self-assessment. The study was conducted on the Srikandi Women's Business Group (UMKM) in Bojongsari Village, Bojongsari District, Purbalingga Regency, with 45 members. The sample size used in this study was 45. The sampling method used was saturated sampling. The data obtained were analyzed using path analysis. The results indicate that education level has a direct effect on self-assessment, while income level does not. Both education and income levels positively influence tax compliance. In addition, self-assessment serves as a mediating variable that strengthens the relationship between education and income levels and tax compliance.